2018
DOI: 10.1136/bmjopen-2018-023520
|View full text |Cite
|
Sign up to set email alerts
|

How common are neurocognitive disorders in patients with chronic kidney disease and diabetes? Results from a cross-sectional study in a community cohort of patients in North Wales, UK

Abstract: ObjectiveChronic kidney disease (CKD) affects nearly 9% of global populations and is strongly associated with older age. Neurocognitive disorders (NCDs), which include mild cognitive impairment and dementia, are rising as a result of ageing populations throughout the world. This investigation’s aim is to report the frequency of mild to major NCD in a clinical cohort of adults with mild to moderate CKD and diabetes.SettingGlan Clwyd District general Hospital, North Wales, UK.ParticipantsWe enrolled 178 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 39 publications
1
8
1
Order By: Relevance
“…Diabetic nephropathy is a major complication and a common cause for chronic kidney disease (CKD) [189], which is significantly associated with cognitive impairment [190,191]. Between 16% and 38% of dialysis patients have cognitive impairment, which is approximately threefold higher than age-matched controls [192]; VaD seems more prominent in CKD than other types of dementias, such as AD [193].…”
Section: Kidney Protectionmentioning
confidence: 99%
“…Diabetic nephropathy is a major complication and a common cause for chronic kidney disease (CKD) [189], which is significantly associated with cognitive impairment [190,191]. Between 16% and 38% of dialysis patients have cognitive impairment, which is approximately threefold higher than age-matched controls [192]; VaD seems more prominent in CKD than other types of dementias, such as AD [193].…”
Section: Kidney Protectionmentioning
confidence: 99%
“…11 The prevalence of cognitive impairment in CKD patients ranges from 17% to 87% depending on severity. [12][13][14][15][16] Its prevalence among CKD patients is 20% in the United Kingdom, 17 75.5% in China, 18 and 53.8% in India. 19 A comparative cross-sectional study in Nigeria showed that the prevalence of cognitive impairment CKD patients is 35.3% whereas for the control group it is 6%.…”
Section: Introductionmentioning
confidence: 99%
“…Of the few studies in diabetic patients with CKD, Liao et al [22] demonstrated that 35% of patients undergoing PD had CI, but the cognitive function was comparable between diabetic patients without retinopathy and nondiabetic patients. Another cohort study showed that 48% of diabetic patients with CKD stage 3 or 4 had neurocognitive disorders [23]. In the general population with DM, a longitudinal cohort study conducted in northern Manhattan reported that 42.5% of diabetic patients had incident CI [15].…”
Section: Discussionmentioning
confidence: 99%